Snakebites in Turkey: epidemiological and clinical aspects between the years 1995 and 2004 - Cesaretli,Y (2010)
The venom of poisonous snakes comprises a complex mixture of several proteins with other less significant constituents, resulting in principles capable of changing viable tissues. The hemotoxic factor is the main responsible for necrosis and tissue sloughing. Envenomations are common in rural areas of Turkey caused by snake species that present hepatotoxic venom, which causes local swelling, ecchymosis and alterations in blood profile. The epidemiological and clinical findings of snake envenomations in Turkey were evaluated based on data recorded by the National Poison Information Center (NPIC) between 1995 and 2004, in a total of 550 snakebite cases. The month of peak incidence was June (24.3%) while most incidents occurred in Marmara, Central Anatolia and Black Sea regions of Turkey. The victims were mainly adults (54.1%). Hospitalized patients displayed clinical signs of local (75.2%) and systemic effects (24.7%). Local clinical symptoms comprised edema, pain, hyperemia, numbness and ecchymosis, while systemic clinical symptoms included nausea, vomiting, hypotension, tachycardia, dyspnea, dry mouth, paresthesia, generalized edema, cyanosis and compartment syndrome. Occasionally, convulsions, confusion, loss of consciousness, hyperthermia, hepatic and circulation failure, hematoma, drowsiness, epistaxis, chest and abdominal pain, venous spasm, thrombocytopenia and bradycardia were recorded. Approximately one third (34.2%) of the patients were treated symptomatically, while 10.5% required antivenom therapy along with symptomatic treatments and 26.3% of all patients were exclusively treated with antivenom. Although a significant number of incidents were reported, no deaths occurred. These findings emphasize the presence of multiple medically important snake species in Turkey and that public awareness and therapeutic approaches appear sufficient to manage snakebite incidents.